Arthroscopic Soft Tissue Stabilization for Traumatic Anterior Shoulder Instability in Elite Collision Athletes. Issue 3 (31st March 2019) - Shota, Hoshika; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Tokai, Morihito; Ueda, Yusuke; Hamada, Hiroshige
Objectives: Surgical options for shoulder instability in collision athletes remain controversial. Although arthroscopic soft tissue stabilization is widely accepted treatment for traumatic anterior shoulder instability, many surgeons prefer coracoid transfer such as Latarjet procedure for collision athletes with or without glenoid defect due to potential high recurrence rate after arthroscopic soft tissue Bankart repair (ABR). In the meantime, Hill-Sachs remplissage (HSR) has been gaining popularity as an effective arthroscopic augmentation procedure. Since 2002, we performed rotator interval closure (RIC) as an augmentation in addition to ABR or arthroscopic bony Bankart repair (ABBR) for collision athletes and obtained satisfactory outcome. However, teen players demonstrated higher recurrence rate compared to twenties and thirties. Therefore, from 2012, we performed HSR as an additional augmentation for teen players besides ABR/ABBR and RIC. The purpose of this study was to assess the outcomes after arthroscopic stabilization in collision athletes who underwent shoulder stabilization under our treatment strategy. Methods: Between 2012 through 2015, 95 consecutive collision athletes underwent shoulder stabilization. Among those, only 2 patients (2%) underwent arthroscopic bony procedure for poor capsular integrity. Among the remaining 93 patients who underwent soft tissue stabilization, 65 were available for minimum 2-year follow-up (70%). Therefore, subjects consisted of 65 players including 54 rugby and 11 American football players (Table 1). There were 13 national top league, 24 collegiate, 21 junior or senior high school, and 7 recreational players. The mean age at surgery was 20 years (range, 16-36). The mean follow-up was 37 months (range, 24-64). We retrospectively reviewed intraoperative findings and surgical procedures using patient records including surgical reports and videos. We also investigated functional outcome and recurrence rate. Pre- and postoperative Rowe scores were compared using paired t test. Results: Preoperative 3DCT of the glenoid demonstrated bony Bankart (fragment type) in 43 players (66%), attritional type in 16 (25%), and normal glenoid in 6 (9%). Mean glenoid bone loss was 15% (range, 0-25) and all of the glenoid with more than 10% bone loss retained bony fragment. All 65 players demonstrated Bankart lesion and 15 had concomitant SLAP lesion (23%) which required to be repaired. In addition, 5 players demonstrated capsule tear (8%), which were also repaired. Twenty-four players (36%) underwent ABR or ABBR with RIC and forty one players (64%) underwent ABR or ABBR combined with HSR (Table 1). The mean Rowe score significantly improved after surgery from 65 (range, 55-75) to 92 (range, 65-100) (P < .001). Recurrence appeared in 2 cases (3%), both of which were junior or senior high school players who underwent ABR with HSR. Ten national top league players who underwent ABR with RIC had no recurrence. Conclusion: Soft tissue stabilization combined with selective augmentation procedures for traumatic shoulder instability in collision athletes demonstrated satisfactory outcomes with extremely low recurrence rate. Since the incidence of having bony Bankart lesion in collision athletes was very high, arthroscopic bony Bankart repair worked in many patients even with significant glenoid bone loss. Further, Hill-Sachs remplissage seemed to be effective additional augmentation especially in young collision athletes. Table 1. Total ABR/ABBR with RIC ABR/ABBR with HSR Players 65 24 41 National top league 13 10 3 College league 21 8 16 Junior or senior high school 21 3 18 Recreational level 7 3 4 Age at surgery (years) 20 (16-36) 25 (15-36) 19 (15-28) Mean follow up (months) 37 (24-64) 41 (24-64) 35 (24-60) Revision surgery 5 1 4